ROLE OF SOCIAL WORK IN SUSTAINABLE DEVELOPMENT: TOWARDS ECO-SOCIAL PRACTICE - Saini, Shubham; Singh, Navneet Prakash (ShodhKosh: Journal of Visual and Performing Arts, 2023)
A social work is a profession in which works and tasks are performed by utilising available resources from social environment namely social networks and support system that enhances humans to thrive and excel their lives. However, in the current trends there are some drawbacks in the manner of work such as very limited engagement of social organisation that focuses on environmental aspects and sustainable ecology. As a consequence, social work has to develop theoretical framework to incorporate ecological environment because man and environment are crucial and mutual dependence components. In the existing ecological hardship, climate change is a matter of concern as it regulates the land fertility and biodiversity to achieve sustainable food productions, cycle of energy and water resources. The ill effects of climate change are unbearable by all, for instances people of Flanders in Belgium with enormous wealth had to face challenges in shrinking free land spaces, environment pollutions and many health issues. And as mentioned by the United Nations Development Programme these crises are mostly affected by the poor people which sets a wide gap between the rich and the poor in both the ecological and economic crises. All of these present major challenges to the social work despite of keeping social justice as central core of frame work.